ANALISIS TATA RUANG TEMPAT PENYIMPANAN DOKUMEN REKAM MEDIS PASIEN DITINJAU DARI ASPEK ANTROPOMETRI PETUGAS REKAM MEDIS - Anggy Pramudhita Putri; Endang Triyanti; Dedi Setiadi (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2014)
AbstractBackground of research that filing officers have difficulty in taking medical record documents because ofhaving to take this documents alternately in the same shelf. It caused by distance between the shelf whichadjacent. Moreover, there are complaint stiff in hands and feet maybe discrepancy between layout with officersanthropometric. The purpose of this research is analyze of layout involve high, long and width of shelf, distancebetween shelf and wide of area reviewed from the anthropometric aspect of medical record officers involve thereach of hand to above, length of arm and width of shoulder. Design of this research is descriptive. Sample ofthis reseacrh is outpatient filing officers as much as 6 persons and taken by total sampling. Result of researchfor size of outpatient filing officers layout dr. Soekardjo General Region Hospital Tasikmalaya City whichadapted with anthropometric data of outpatient filing officers are high of shelf 180 cm after adapted thensize become 185,5 cm, long of shelf 229,5 become 142,5 cm, width of shelf 50 cm become 54 cm, distancebetween shelf 63 cm become 102 cm, wide of area 32,06 m2 after adapted become 35,69 m2. The result of sizefrom measurement in dr. Soekardjo General Region Hospital Tasikmalaya City is smaller than size that gotfrom measurement result. It can be analyzed that condition of room in dr. Soekardjo General Region HospitalTasikmalaya City inadequate and inappropriate with size of body dimension outpatient filing officers. It willbe better if condition of room was adapted with anthropometric data of outpatient filing officers, so officersfeel more comfortable in doing his job.Keywords : Layout, Medical Record Document Storage, Anthropometric of Medical Record OfficersAbstrakPenelitian ini bertujuan untuk menganalisis tata ruang meliputi tinggi rak, panjang rak, lebar rak, jarak antarrak dan luas ruangan ditinjau dari aspek antropometri petugas rekam medis meliputi jangkauan tangan ke atas,panjang depa dan lebar bahu. Jenis Penelitian yang digunakan bersifat deskriptif. Sampel penelitian ini ialahpetugas filing rawat jalan sebanyak 6 orang yang diambil secara total sampling. Hasil penelitian ini adalah untukukuran tata ruang filing rawat jalan di RSUD dr. Soekardjo Kota Tasikmalaya yang disesuaikan dengan dataantropometri petugas filing rawat jalan ialah tinggi rak 180 cm setelah disesuaikan maka ukuran menjadi 185,5cm, Panjang rak 229,5 cm disesuaikan menjadi 142,5 cm, Lebar rak 50 cm disesuaikan menjadi 54 cm, Jarakantar rak 63 cm disesuaikan menjadi 102 cm, luas ruangan 32,06 m2 setelah disesuaikan menjadi 35,69m2.Ukuran yang dihasilkan dari pengukuran di RSUD dr. Soekardjo Kota Tasikmalaya lebih kecil dibandingkanukuran yang diperolah dari hasil perhitungan. Hal itu dapat dianalisis bahwa keadaan ruangan di RSUD dr.Soekardjo Kota Tasikmalaya kurang memadai dan belum sesuai dengan ukuran dimensi tubuh petugas filingrawat jalan. Alangkah baiknya apabila kondisi ruangan disesuaikan dengan data antropometri petugas filingrawat jalan sehingga petugas merasa lebih nyaman dalam melakukan pekerjaannya.Kata kunci : Tata Ruang, Tempat Penyimpanan, Antropometri